A review of models for water level forecasting based on machine learning - Wee W.J.; Zaini N.B.; Ahmed A.N.; El-Shafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
forecasting method; literature review; machine learning; numerical model; reservoir; water level; water resource